Renovating Science Professional Development to Meet Teachers’ Needs - Julie Thiele; Ollie Bogdon (The Advocate, 2020)
In order to meet the needs of elementary in-service teachers, renovated professional learning, including the components of the Effective Science Professional Development Model is vital. Increasing teachers’ pedagogical content knowledge, engaging teachers in investigations, school-year coaching with the underlying theme of collaboration are encompassed in the four key components of the renovated model. Experiences shared in the article, the successes and challenges of implementing professional development with the focus of shifting science education to hands-on investigations in doing science, provide leaders in science education the opportunity to explore effective professional development opportunities and utilize this model in their schools to enhance the teaching and learning of science education.
Keywords: Science; professional development; learning communities